2019
DOI: 10.1186/s12929-019-0512-2
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: roles in intestinal mucosal homeostasis and inflammation

Abstract: The intestinal mucosa is a site of multiple stressors and forms the barrier between the internal and external environment. In the intestine, a complex interplay between the microbiota, epithelial barrier and the local immune system maintains homeostasis and promotes a healthy gut. One of the major cellular catabolic processes that regulate this homeostasis is autophagy. Autophagy is required to maintain anti-microbial defense, epithelial barrier integrity and mucosal immune response. Dysregulation of the autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 119 publications
1
108
0
1
Order By: Relevance
“…In addition to immune markers, recently, significant emphasis has been placed on studying the role of autophagy in mediating intestinal inflammation, and genetically modified animal models have been created to study this phenomenon. Autophagy is an evolutionarily conserved, catabolic cellular mechanism whereby cytoplasmic contents are delivered to, and degraded in, the lysosome (176,177). A link between autophagy and intestinal inflammation has been proposed, and genome-wide association studies have identified the gene encoding ATG16L1, an autophagy-related protein, as a susceptibility locus for CD (178).…”
Section: Genetic Modelsmentioning
confidence: 99%
“…In addition to immune markers, recently, significant emphasis has been placed on studying the role of autophagy in mediating intestinal inflammation, and genetically modified animal models have been created to study this phenomenon. Autophagy is an evolutionarily conserved, catabolic cellular mechanism whereby cytoplasmic contents are delivered to, and degraded in, the lysosome (176,177). A link between autophagy and intestinal inflammation has been proposed, and genome-wide association studies have identified the gene encoding ATG16L1, an autophagy-related protein, as a susceptibility locus for CD (178).…”
Section: Genetic Modelsmentioning
confidence: 99%
“…Ions such as Na + , Cl − , K + , and H + and metals such as Fe 2+ are transported by channels, symporters, and antiporters such as Na + /H + antiporter NHE1 and the Cl − channel CFTR [14]. Macromolecules such as intact proteins are transported by a variety of receptor-mediated endocytic mechanisms [15]. Intact bacteria, antigens, and particulate matter are transported by specialized M-cells overlying intestinal lymphoid aggregates (Peyer's patches) in the distal small intestine [16][17][18] and are sensed by goblet cell-associated antigen pathways (GAPs) [19], with some data indicating that LPS is absorbed through the lamina propria by GAPs in the small intestine [20].…”
Section: Overview Of Intestinal Mucosal Structure and Barrier Functionmentioning
confidence: 99%
“…Autophagy is a key process responsible for maintenance of intestinal physiology by controlling function of the various intestinal cells. Autophagy is important for preventing the invasion and dissemination of pathogens, maintaining barrier integrity, preserving intestinal homeostasis, and controlling mucosal inflammation [ 81 ]. Therefore, to investigate whether autophagy could be activated in Caco-2 cells upon BGKMJ1-36/BGVLJ1-21 yogurt treatment, we performed qPCR analysis of genes involved in different steps of the autophagy process, including autophagy induction ( ULK1 ), autophagosome formation ( AMBRA, BECN1 , PIK3C3 , UVRAG ), autophagosome expansion ( ATG5 , GABARAP, MAP1LC3B ), and retrieval of autophagic proteins ( SQSTM1 ) [ 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%